Randomized controlled trial of an Acceptance and Commitment Therapy and compassion-based group intervention for persons with inflammatory bowel disease: the LIFEwithIBD intervention - Ferreira, Cláudia; Pereira, Joana; Skvarc, David; Oliveira, Sara; Galhardo, Ana; Ferreira, Nuno B.; Lucena-Santos, Paola; Carvalho, Sérgio A.; Matos-Pina, Inês; Rocha, Bárbara S.; Portela, Francisco; Trindade, Inês A. (Frontiers in Psychology, 2024)
CF (PI) and IAT (Co-PI) designed and wrote the project's proposal, obtained funding and provided study oversight. CF, JP, and DS wrote the first draft of the manuscript. DS performed data analysis. All authors edited and provided feedback on this manuscript and approved its final version.This project was peer-reviewed in the context of the 2017 R&D projects Grant call of the Portuguese Foundation for Science and Technology (Fundação para a Ciência e Tecnologia), having successfully been granted funding (Grant No. PTDC/PSI-ESP/28602/2017).The data, analytic methods, and study materials that support the findings of this study are available from the corresponding authors upon reasonable request.